Active railway suspension controllers using electro-mechanical actuation technology - Md. Yusof, Hazlina; R. M., Goodall; R., Dixon (2010)
The paper looks at the effects of real actuator dynamics in a railway suspension. With the actuators are placed in the front and rear of the secondary suspensions vehicle body, the performance of real actuators in secondary suspension is investigated. The performance of an electromechanical actuator (EMA) in the active railway secondary suspension for ride quality improvement is also addressed. The degradation in ride quality is highlighted when the actuator dynamics is included in the active suspension system regardless of the suspension control strategy used.